2020
DOI: 10.1155/2020/8822595
|View full text |Cite
|
Sign up to set email alerts
|

Study on Control Technology for Working Faces Passing through Long-Span Abandoned Roadways

Abstract: The width of an abandoned roadway has a great influence on the roof stability of the working face. According to the coal seam conditions of the 30106 working face in the Sanyuan Shiku mine, the advance of a working face through an abandoned roadway was studied by using theoretical analysis, similar material simulation, numerical simulation, and field testing to determine the law of stope roof fracture migration, the stress distribution characteristics, and the variation in support resistance. Several conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Yang [7] examined the roof failure characteristics, forces acting on supports, and action characteristics of abutment stress observed in front of a longwall face when an AR was installed in front of a cave working face. A solution for roof presplit in the AR was proposed by Liu [8], and the research results indicated that the roof vertical stress and vertical displacement could be reduced effectively by roof presplit. Ma [9] studied the occurrence mechanism of advanced coal pillar instability failure and support crushing accidents during a long-wall face passing AR period, and put forward the occurrence mechanism and prevention measures.…”
Section: Introductionmentioning
confidence: 99%
“…Yang [7] examined the roof failure characteristics, forces acting on supports, and action characteristics of abutment stress observed in front of a longwall face when an AR was installed in front of a cave working face. A solution for roof presplit in the AR was proposed by Liu [8], and the research results indicated that the roof vertical stress and vertical displacement could be reduced effectively by roof presplit. Ma [9] studied the occurrence mechanism of advanced coal pillar instability failure and support crushing accidents during a long-wall face passing AR period, and put forward the occurrence mechanism and prevention measures.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions such as surrounding rock instability mechanism and support method are obtained, which provide theoretical basis and guidance for related similar roadways. Indoor experiment simulation has irreplaceable advantages, many scholars [8][9][10][11][12] and embarked on the indoor simulation of similar materials selection research, to a variety of mechanical properties of the model test, the research and the relationship between the mechanical properties of ratio, the constitutive model is set up, put forward the model test collection and monitoring methods, etc. With the increase of disaster events in deep tunnels, many scholars 13,14 have conducted research on them and carried out stability research on deep tunnels subjected to high ground stress and strong dynamic disturbance through numerical simulation.…”
mentioning
confidence: 99%